2020
DOI: 10.20944/preprints202012.0287.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prognostic Value of Whole-Blood PSMB5, CXCR4, POMP and RPL5 mRNA Expression in Patients with Multiple Myeloma Treated with Bortezomib

Abstract: Proteasome inhibitors, like bortezomib, play a key role in the treatment of multiple myeloma (MM); however, most patients eventually relapse and eventually show multiple drug resistance, and the molecular mechanisms of this resistance remain unclear. The present study examines the expression of previously-described genes that may influence resistance to bortezomib treatment at the mRNA level (ABCB1, CXCR4, MAF, MARCKS, POMP, PSMB5, RPL5, TXN and XBP1). mRNA expression was determined in 73 MM patients treated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
1
Order By: Relevance
“…There are also reports demonstrating that some cell lines resistant to bortezomib have increased expression of POMP [12,29]. It has been previously documented that serum POMP mRNA was significantly up-regulated in MM patients refractory to bortezomib-based treatment [30]. However, in the present study, bortezomib sensitive and refractory patients demonstrated similar levels of POMP expression in MM at the protein level, probably due to the relatively low number of patients.…”
Section: Discussioncontrasting
confidence: 60%
“…There are also reports demonstrating that some cell lines resistant to bortezomib have increased expression of POMP [12,29]. It has been previously documented that serum POMP mRNA was significantly up-regulated in MM patients refractory to bortezomib-based treatment [30]. However, in the present study, bortezomib sensitive and refractory patients demonstrated similar levels of POMP expression in MM at the protein level, probably due to the relatively low number of patients.…”
Section: Discussioncontrasting
confidence: 60%